Seroprevalence of small ruminant brucellosis in the state of Qatar - Hashim Alhussain; Ahmed Gawish; Susu Zughaier; Abdulaziz M. Al‐Zeyara; Hadi M. Yassine; Asmaa Al Thani; Nahla O. Eltai (Veterinary Medicine and Science, 2024)
Abstract Background Brucellosis is one of the most important zoonotic diseases worldwide, with a significant economic and health burden. The disease is endemic in many regions around the world. Data regarding the disease in the Arabic Gulf region is scarce, and a limited number of studies have been conducted in Qatar. This study is the first to investigate the seroprevalence of small ruminant brucellosis in the state of Qatar. Methods The country was divided into three zones based on animal population (high, medium and low). A total of 494 blood samples from 57 small ruminant flocks were randomly collected from the three zones. Rose Bengal and competitive enzyme‐linked immunosorbent assay were used to investigate the apparent and true seroprevalence at both the animal and flock levels. A regression model was used to investigate the potential risk factors, including geographic zone, sex and age. Results At the animal level, the overall (sheep and goat) apparent and true seroprevalence were 9.6% (95% confidence interval [95% CI]: 7.3–12.5) and 8.4% (95% CI: 5.9–11.5), respectively. In sheep, the apparent seroprevalence was 16.7% (95% CI: 12.5–21.8), and the true seroprevalence was 16.1% (95% CI: 11.6–21.7), whereas in goats, the apparent seroprevalence was 2.4% (95% CI: 1.1–5.2), and the true seroprevalence was 0.7% (95% CI: −0.7 to 3.7). At the flock level, overall, apparent sheep and goat seroprevalence were 19.3% (95% CI: 11.1–31.3), 30.0% (95% CI: 16.1–49.8) and 7.4% (95% CI: 2.1–23.4) and true seroprevalence was 18.9% (95% CI: 10.1–31.9), 30.5% (95% CI: 16.1–49.8) and 6.1% (95% CI: 0.3–23.3) respectively. Univariable regression analysis revealed age as the only significant risk factor in the sampled population. Conclusions Brucella appears to be endemic to small ruminants in Qatar. The findings of this study provide baseline data regarding small ruminant brucellosis in Qatar and will aid in plans to control and eradicate the disease.